Factors influencing intention to use Islamic credit cards in Selangor - Abdul Razak, Dzuljastri; Ahmad Faris, Ammar; Mohamed Sharif, Mohammad Syarwan; E Azam, Md Siddique (Universiti Utara Malaysia, 2019)
Islamic credit card (ICC) has been widely used for personal consumption. The use of ICC is gaining prominence as an alternative to conventional credit card as the concept and operations are permissible by the shariah. The paper aims to determine factors influencing intention to use ICC based on three variables namely benefits, fair charges and religious motivation. A quantitative methodology was conducted via a survey of 102 respondents in the state of Selangor. The results indicated that benefits and religious motivations have significant influence on the intention to use Islamic credit cards. Hence, practitioners should incorporate the two factors in their marketing efforts to promote ICC. The academician can benefit by conducting further research on this eminence body of knowledge.